2020
DOI: 10.1155/2020/6394625
|View full text |Cite
|
Sign up to set email alerts
|

Wasp Venom Possesses Potential Therapeutic Effect in Experimental Models of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease. Wasp venom (WV), which is considered as a traditional folk medicine in Jingpo nationality in Yunnan, China, relieves rheumatoid arthritis. The current study aimed to investigate the effect of wasp venom ameliorating rheumatoid arthritis symptoms in experimental rats. We established a model of type II collagen- (CII-) induced arthritis (CIA) in SD rats and examined the inhibition of inflammation and autoimmune response. The antiarthritic effects of WV were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Doses of 0.05, 0.2 and 0.6 mg/kg were selected as evidenced by our previous study (Gao et al. 2020 ) and other reports (Kim et al. 2016 ; Badawi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doses of 0.05, 0.2 and 0.6 mg/kg were selected as evidenced by our previous study (Gao et al. 2020 ) and other reports (Kim et al. 2016 ; Badawi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results showed that the wasp venom extracted from Vespa magnifica Smith (Vespidae) had a protective effect on rheumatoid arthritis in rats (Gao et al. 2020 ). Additionally, compounds extracted from the wasp venom have also been used to treat major neurological disorders, including epilepsy (Mortari et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, IL6 was the key accelerator in the final differentiation of B-cells into Ig-secreting cells, and IL8 had the function on neutrophil activation [ 17 ]. IL6 and IL8 could take part in a wide variety of inflammation-associated disease by inducing the inflammatory response, such as rheumatoid arthritis [ 18 ], ulcerative colitis [ 19 ], and acute pancreatitis [ 20 ]. In acute pancreatitis, the levels of these cytokines in peripheral blood were abnormally increased and significantly associated with the disease development.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the drugs on the market are derived from plants [ 19 ]. However, the list of extracts and molecules isolated from animals is increasing [ 20 , 21 ]. RPLO is used by the Guarani-Kaiowá community and other indigenous communities for food [ 7 ] and medicinal purposes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%